Islam dan Sain: Telaah Terhadap Islamisasi Ilmu Pengetahuan dan Pengilmuan Islam - Kasori; Ikke Fitriana Nugrahini; Aulia Arsinta (Al-Abshor : Jurnal Pendidikan Agama Islam, 2024)
This article discusses the Relations of Islam and Science by examining the Islamization  of  Science  Syed Muhammad  al-Naquib  al-Attas,  Kuntowijoyo Islamic    Studies    and    the    Paradigm    of    Interconnection    Integration-Transintegration of Science Amin Abdullah. The method used in this research is descriptive-qualitative method, and is  included  in  the  literature  research.  The process of collecting data in this study is by observing, in the sense of tracking various references that have relevance regarding the focus of the study, both from books, articles, and so on that function to support these data. The data analysis technique used in this research is the content analysis method. From the studies conducted,  it  can  be  seen  that  First,  there  are  two  similarities  between  the Islamization   of   science,   Islamic   scholarship   and   the   trans-integration   of knowledge, namely both being an Islamic response to the development of science and both rejecting secularism. Second, the difference between the Islamization of knowledge, Islamic scholarship and the transtegration of knowledge lies in  the emphasis and details of the key concepts. The Islamization of science places more emphasis on Islam, Islamic scholarship places more emphasis on science, while the integration   of   interconnections   tends   to   be   more   balanced   in   seeing   the relationship  between  Islam  and  science.   Third,   the  difference  between   the Islamization   of   knowledge,   Islamic   scholarship   and   the   transtegration   of knowledge occurs because of differences in background between the three.  The Islamization  of  knowledge  was  initiated  by people  who  were  traumatized  by colonialism, while Islamic scholarship and the transtegration of knowledge were not. Abstrak Artikel ini membahas tentang Relasi Islam dan Sains dengan mengkaji Islamisasi Sains Syed Muhammad al-Naquib al-Attas, Kajian Islam Kuntowijoyo dan Paradigma Integrasi Interkoneksi— Transintegrasi Sains Amin Abdullah. Metode yang digunakan dalam penelitian ini adalah metode deskriptif-kualitatif, dan termasuk dalam penelitian kepustakaan.  Proses pengumpulan data dalam penelitian ini adalah dengan cara observasi, dalam arti menelusuri berbagai referensi yang mempunyai relevansi mengenai fokus penelitian, baik dari buku, artikel, dan lain sebagainya yang berfungsi untuk mendukung data tersebut. Teknik analisis data yang digunakan dalam penelitian ini adalah metode analisis isi. Dari kajian yang dilakukan terlihat bahwa Pertama, terdapat dua kesamaan antara Islamisasi ilmu pengetahuan, keilmuan Islam dan transintegrasi ilmu pengetahuan, yaitu keduanya merupakan respon Islam terhadap perkembangan ilmu pengetahuan dan sama-sama menolak sekularisme. Kedua, perbedaan Islamisasi ilmu, keilmuan Islam, dan transintegrasi ilmu terletak pada penekanan dan rincian konsep-konsep kuncinya. Islamisasi ilmu pengetahuan lebih menekankan pada Islam, keilmuan Islam lebih menekankan pada ilmu pengetahuan, sedangkan integrasi interkoneksi cenderung lebih seimbang dalam melihat hubungan antara Islam dan ilmu pengetahuan.   Ketiga, perbedaan Islamisasi ilmu, keilmuan Islam, dan transintegrasi ilmu terjadi karena perbedaan latar belakang ketiganya.  Islamisasi ilmu pengetahuan diprakarsai oleh masyarakat yang trauma dengan kolonialisme, sedangkan keilmuan Islam dan transintegrasi ilmu pengetahuan tidak.